Evaluation of the Community Cataract Surgical Services of a University Teaching Hospital Using Cataract Surgical Coverage in Nigeria - Olokoba, L (Ethiop J Health Sci, 2016)
BACKGROUND: Cataract is the leading cause of blindness in the world. An efficient and effective cataract surgical service is necessary to reduce the backlog of cataract blindness in the community. This study aims to determine the cataract surgical coverage among individuals aged 50 years and above residing in Esie and Arandun communities. This will serve as a measure of the impact of the cataract intervention programme provided by the University of Ilorin Teaching Hospital, Nigeria. METHODS: The study was a population-based, cross sectional survey conducted from November to December, 2013. Cataract surgical services are provided by the University of Ilorin Teaching Hospital, Nigeria, at Esie and Arandun communities as out-reach centres. Seven hundred and fifty-five individuals aged 50 years and above residing in these communities had basic ocular examination done. RESULTS: Out of the 765 subjects registered, 755(98.7%) were examined. Out of these, 38.4% were males and 61.6% were females. The prevalence of bilateral cataract blindness was 1.6%. The Cataract Surgical Coverage (eyes) at visual acuity < 3/60 for males and females were 52.3% and 51.2% respectively (X2=19.30, p=0.001), while the Cataract Surgical Coverage (person) at visual acuity less < 3/60 for males and females were 80.6% and 68.4% respectively (X2=2.10, p=0.147). CONCLUSION: The Cataract Surgical Coverage was high with a correspondingly low prevalence of cataract blindness in these communities. The availability of cataract surgical services via out-reach programmes bridges the gap between eye care-givers and the community.